PENGARUH KESULITAN KEUANGAN, KEGAGALAN HUTANG DAN MASA AUDIT TERHADAP OPINI AUDIT GOING CONCERN ( Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2022 ) - SARI, ANJELITA; GITA SUCI, RAMA; PUTRI, ANNIE MUSTIKA (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
In assessing a company's ability to maintain its business continuity, this is known as a going concern audit opinion. This research aims to find out and test how financial disstress, debt default, and audit tenure influence going concern audit opinions on companies listed on the Indonesia Stock Exchange in 2021-2022. This research method uses quantitative methods. In determining the research sample, a purposive sampling technique was used, thus obtaining 53 samples from 778 populations. Data collection uses documentation studies and uses logistic regression analysis as a data analysis method. The results of the research analysis reveal that financial disstress have an effect on going concern audit opinion, while debt default and audit tenure have no effect on going concern audit opinion.